RELEVANSI PENDIDIKAN ISLAM PERSPEKTIF GUS DUR DI ERA MILENIAL - Rizal Zakaria; Muhammad Ahlun Naza; Ahmad Mushofihin; Ulfa Rahmawati (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2020)
One of the most important matters discussed is about Islamic Education, especially for Muslims today. Islamic education always develops according to changing times, for that reason, Islamic education must be designed to follow the path of change, so as not to be left behind by the development of the era itself. Regarding this matter, Gus Dur has discussed Islamic education with his thoughts which are closely related to the concepts of multicultural education, neomodernism and liberation which are very relevant to the conditions of the times in the millennial era today. It is therefore important to know the relevance of Gus Dur's perspective of Islamic education in the millennial era. This research is a qualitative research type of library (library reseach), data collection techniques using methods that rely on reference studies and study of literary texts with descriptive and historical approaches from the source, namely: books, journals and articles related to the topic of discussion. From the results of this study it can be concluded that the thinking of K.H. Abdurrahman Wahid regarding Islamic education is very relevant to the times in the millennial era, especially in Indonesia.